Pendekatan Cognitive Behavioral Therapy (CBT) Teknik Reframing Sebagai Upaya Meningkatkan Regulasi Emosi Remaja di SMP Negeri 14 Palu - Putri Inayah; Ridwan Syahran; Azam Arifyadi; Dhevy Puswiartika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to identify the effect of providing individual counseling services on reframing techniques to improve adolescent emotional regulation in students at SMP Negeri 14 Palu. The subjects of this study were class VIII students at SMP Negeri 14 Palu with 6 samples divided into 2 groups, namely 3 samples in the experimental group and 3 samples in the control group. The instrument used is a Likert scale questionnaire consisting of 24 items which is an instrument adapted by researchers based on aspects of emotion regulation theory according to Gratz and Roamer 2004. The data that has been obtained is then processed and analyzed using descriptive and inferential methods with the Mann Whitney Test formula. The results of descriptive analysis show that before the provision of individual counseling services reframing techniques there were 6 students who had emotional regulation that was not included in the high classification. After being given individual counseling services, reframing techniques, there were 3 students in the experimental group who experienced a significant increase in emotional regulation compared to 3 other students in the control group. The results of the inferential analysis indicate that the obtained significance value is 0.043, which means that the significance value is < 0.05. So it can be concluded that the null hypothesis (Ho) which reads